Convict Criminology - Inside and Out - Earle, Rod (2016)
Convict criminology is the study of criminology by those who have first-hand experience of imprisonment. This is the first single authored book to trace the emergence of Convict Criminology and explore its relevance beyond the USA to the UK and other parts of Europe. Addressing epistemological issues of ‘insider research’, it presents uniquely reflexive scholarship combining personal experience with critical perspectives on contemporary penality. Focussing explicitly on men, it covers: • the way prisoners, ex-prisoners and prison research contribute to criminological knowledge • historical figures in criminology whose prison experiences are rarely recognised • the way racism, colonialism and class shape penal experience and social worlds Drawing from his own experience of imprisonment, prison research and criminology, the author demonstrates how this experience can expand the criminological imagination. It is a novel and compelling account for students, teachers, academics and penal practitioners. It will inform, educate and entertain anyone working in criminal justice, legal and para-legal professions and those with an interest in social justice